Absence of mature microRNAs inactivates the response of gene expression to carcinogenesis induced by N‐ethyl‐N‐nitrosourea in mouse liver. Issue 12 (30th January 2014) - Luan, Yang; Qi, Xinming; Xu, Liang; Ren, Jin; Chen, Tao
ABSTRACT This study aims to evaluate the role of microRNAs (miRNAs) in chemical tumorigenesis by evaluating genomic gene expression in miRNA knockout mice. Previous studies showed that mice without mature miRNAs due to hepatocyte‐specific Dicer1 knockout (KO) had a much higher liver tumor incidence than wild‐type mice. In this study, Dicer1 KO or the wild‐type mice were treated intraperitoneally with genotoxic carcinogen N‐ethyl‐N‐nitrosourea (ENU) at a single dose (150 mg kg–1 that resulted in liver tumorigenesis) or the vehicle at 3 weeks of age. The animals were killed 2 weeks after treatment and the liver samples were collected for the gene expression study. Principal components analysis and hierarchical cluster analysis showed that gene expression was globally altered by the Dicer1 KO and ENU exposure. There were 5621, 3286 and 2565 differentially expressed genes for Dicer1 disruption, ENU treatment in wild‐type mice and ENU treatment in Dicer1 KO mice, respectively. Functional analysis of the differentially expressed genes suggests that the Dicer1 KO mouse liver lost their capability to suppress the carcinogenesis induced by ENU exposure in genomic level. In addition, the miRNA‐mediated BRCA1 and P53 signaling pathways were identified as the main pathways responsible for the tumorigenesis. We conclude that the mouse livers in the absence of mature miRNAs could not appropriately respond to carcinogenic insults from ENU treatment, indicating that miRNAs play a critical role in chemical carcinogenesis. Copyright © 2014 John Wiley & Sons, Ltd.